Cholinesterase alterations in delirium after cardiosurgery: a German monocentric prospective study. Issue 1 (14th January 2020) - Adam, Elisabeth Hannah; Haas, Victoria; Lindau, Simone; Zacharowski, Kai; Scheller, Bertram
Abstract : Objectives: Postoperative delirium (POD) is a common complication after elective cardiac surgery. Recent evidence indicates that a disruption in the normal activity of the cholinergic system may be associated with delirium. Design: Prospective observational study. Setting: Single-centre at a European academic hospital. Primary and secondary outcome measures: In our study the enzyme activities of acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) were determined preoperatively as well as on the first and second postoperative day. The confusion assessment method for the intensive care unit was used to screen patients for the presence of POD. Results: A total of 114 patients were included in the study. POD was associated with a decrease in BChE activity on postoperative day 1 (p=0.03). In addition, patients who developed POD, had significantly lower preoperative AChE activity than patients without POD (p<0.01). Multivariate analysis identified a preoperatively decreased AChE activity (OR 3.1; 95% CI 1.14 to 8.46), anticholinergic treatment (OR 5.09; 95% CI 1.51 to 17.23), elevated European System for Cardiac Operative Risk Evaluation (OR 3.68; 95% CI 1.04 to 12.99) and age (OR 3.02; 95% CI 1.06 to 8.62) to be independently associated with the development of POD. Conclusions: We conclude that a reduction in the acetylcholine hydrolysing enzyme activity in patients undergoing cardiac surgery may correlate with the development of POD.